A revision of Rhodomantis Giglio-Tos, 1917 (Mantodea: Mantidae: Mantinae) - Milledge, Graham A. (Zootaxa, 2014)
The genus Rhodomantis Giglio-Tos is revised. A total of nine species are recognised. Seven new species, R. helenae, R. kimberley, R. macula, R. microptera, R. mitchell, R. napier, and R. rentzi are described. Rhodomantis carinicollis Werner and R. gracilis Tindale are new synonyms of R. queenslandica Sjöstedt.